ACNP White Paper: Update on Use of Antipsychotic Drugs in Elderly Persons with Dementia - Jeste, Dilip V. (2007)
In elderly persons, antipsychotic drugs are clinically prescribed off-label for a number of disorders outside of their Food and Drug Administration (FDA)-approved indications (schizophrenia and bipolar disorder). The largest number of antipsychotic prescriptions in older adults is for behavioral disturbances associated with dementia. In April 2005, the FDA, based on a meta-analysis of 17 double-blind randomized placebo-controlled trials among elderly people with dementia, determined that atypical antipsychotics were associated with a significantly (1.6−1.7 times) greater mortality risk compared with placebo, and asked that drug manufacturers add a ‘black box’ warning to prescribing information for these drugs. Most deaths were due to either cardiac or infectious causes, the two most common immediate causes of death in dementia in general. Clinicians, patients, and caregivers are left with unclear choices of treatment for dementia patients with psychosis and/or severe agitation. Not only are psychosis and agitation common in persons with dementia but they also frequently cause considerable caregiver distress and hasten institutionalization of patients. At the same time, there is a paucity of evidence-based treatment alternatives to antipsychotics for this population. Thus, there is insufficient evidence to suggest that psychotropics other than antipsychotics represent an overall effective and safe, let alone better, treatment choice for psychosis or agitation in dementia; currently no such treatment has been approved by the FDA for these symptoms. Similarly, the data on the efficacy of specific psychosocial treatments in patients with dementia are limited and inconclusive. The goal of this White Paper is to review relevant issues and make clinical and research recommendations regarding the treatment of elderly dementia patients with psychosis and/or agitation. The role of shared decision making and caution in using pharmacotherapy for these patients is stressed.